A comparative study of graphene growth by APCVD, LPCVD and PECVD. (30th March 2018) - Ullah, Zaka; Riaz, Saira; Li, Qi; Atiq, Shahid; Saleem, Muhammad; Azhar, Muhammad; Naseem, Shahzad; Liu, Liwei
Abstract: Graphene films are deposited on Cu foils through atmospheric-pressure chemical vapor deposition (APCVD), low-pressure chemical vapor deposition (LPCVD) and plasma-enhanced chemical vapor deposition (PECVD), and their comparative analysis is performed to explore the most appropriate growth method and experimental conditions. The temperature, pressure and concentration of precursor gases inside the furnace tube are the major factors which directly affect the graphene growth, and by employing APCVD, LPCVD and PECVD, these factors are optimized to achieve the desired growth. For the deposited films, surface morphology is investigated via optical microscopy and scanning electron microscopy, quality of graphene is examined through Raman spectroscopy, transmission measurements are made by employing UV-visible spectroscopy, and sheet resistance of deposited graphene is measured using four-point probe method. In present work, most of the graphene films deposited by APCVD are multilayer, by LPCVD are a few-layer, and by PECVD are monolayer and bilayer. The graphene deposition is also achieved at reduced temperature ∼350 °C using PECVD, which is still among the lowest growth temperatures in the reported literature. The study can be of great significance in achieving the desired growth of graphene and other related materials using CVD.